2017
DOI: 10.1007/s10461-017-1764-z
|View full text |Cite
|
Sign up to set email alerts
|

What do Key Stakeholders Think About HIV Self-Testing in Canada? Results from a Cross-Sectional Survey

Abstract: Human immunodeficiency virus (HIV) self-testing presents an empowering alternative to facility-based testing for reaching undiagnosed HIV infected individuals, but is not currently available in Canada. We surveyed stakeholders (clinical providers, public health professionals, researchers) engaged in HIV testing initiatives nationwide to identify the concerns, opportunities and challenges to implementing HIV self-testing in Canada. An online cross-sectional survey was disseminated by the Canadian Institutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Recently, we surveyed Canadian stakeholders involved in HIV testing initiatives across the country and found that many were in favor of self-testing but were concerned about linkages to care and accuracy of self-tests. Furthermore, HIV self-testing strategies were perceived to pose an economic threat to the prevailing HIV testing models in Canada [13]. While global research on the implementation of HIV self-testing has increased exponentially, few studies have explored self-testing in the Canadian context.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we surveyed Canadian stakeholders involved in HIV testing initiatives across the country and found that many were in favor of self-testing but were concerned about linkages to care and accuracy of self-tests. Furthermore, HIV self-testing strategies were perceived to pose an economic threat to the prevailing HIV testing models in Canada [13]. While global research on the implementation of HIV self-testing has increased exponentially, few studies have explored self-testing in the Canadian context.…”
Section: Introductionmentioning
confidence: 99%
“…Self-testing can be viewed as a competitive option to the rapid testing programs offered in nearly all of the CBO/NGOs that employed our participants, as they both could be targeting similar populations. The results of a study conducted in Canada pointed towards this direction, with stakeholders involved directly in testing activities viewing HIV self-testing as a challenge to current HIV testing delivery models [14]. However, self-testing is rapidly expanding across the world, and the WHO estimated that the global self-test volumes would grow from 1 million in 2017 to an estimated 16.4 million (12.9 million-19.3 million) by the end of 2020 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some qualitative studies aimed at capturing key stakeholders' opinions working in sub-Saharan countries [12,13] identified self-testing as an opportunity to increase testing. In Canada, a study that surveyed stakeholders engaged in HIV testing concluded that stakeholders were generally in favor of self-testing [14] but results were not provided by stakeholder type. Additionally, the difference between the opinions of stakeholders and PUs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This will require sustained collaboration with private providers, pharmacies, community-based organizations, public clinics, test manufacturers and laboratories. 12 Third, addressing the economics of integration of HIVST service delivery is key to sustainability. The Canadian health systems are largely operated provincially and combine public and private care.…”
Section: Key Pointsmentioning
confidence: 99%